Genetic correlations between visual scores and carcass traits measured by real-time ultrasound in beef cattle - Yokoo, Marcos Jun Iti; Werneck, Juliana Nunes; Pereira, Márcio Cinachi; Albuquerque, Lucia Galvão de; Koury Filho, William; Sainz, Roberto Daniel; Lobo, Raysildo Barbosa; Araujo, Fabiano Rodrigues da Cunha (Pesquisa Agropecuaria Brasileira, 2010)
The aim of this work was to evaluate the genetic and phenotypic correlations between carcass traits measured by real-time ultrasound and by visual scores, in order to verify the effectiveness of these scores in determining muscularity and carcass fat. Carcass traits measured by real-time ultrasound were longissimus muscle area (LMA) and backfat thickness (BF), obtained between the 12th and 13th ribs, as well as the rump fat thickness (RF). The visual scores for the traits of body structure (E), precocity (P), and muscle (M) were evaluated individually. The genetic and phenotypic parameters were estimated by multivariate analysis, using restricted maximum likelihood methodology. The estimated genetic correlations between LMA and E, P and M were 0.54, 0.58 and 0.61, respectively, indicating that, in the long term, the use of LMA as a selection criterion might produce animals with higher visual scores. Similar genetic correlations were found between both subcutaneous fat measures (BF and RF) and P and M scores. However, genetic correlations between both subcutaneous fat measures and E were close to zero. The phenotypic correlations followed the same trends of their respective genetic correlations. These estimates indicate that the visual scores and LMA are, in part, determined by the same groups of genes.